PENINGKATAN MUTU PENDIDIKAN MADRASAH MELALUI MANAJEMEN SDM: (STUDI PENELITIAN MAN 2 MAJALENGKA) - Dede Rosada Kolbi; Suklani Suklani (CV. ADIBA AISHA AMIRA, 2023)
The quality of Madrasah education, especially at MAN 2 Majalengka at the present time is still not very promising, it is even considered to be stagnant and has not experienced improvement, so an appropriate and correct step is needed from the Principal in managing Madrasah one of which is managing its human resources so that good quality education is achieved. This study used a qualitative descriptive method, namely research into the field and then studied for implementation of corrective changes through established regulations. The purpose of this research is to improve the quality of education at MAN 2 Majalengka through more optimal human resource management. So that the results of his research show that one of the factors in improving the quality of education is the active and effective role of the head of the Madrasah in managing his human resources so that the active role of human resources in advancing and improving the quality of education is created.